Neopapillarine, an unusual coumarino-alkaloid from the root extract of neocryptodiscus papillaris with cytotoxic activity on renal cancer cells - Tosun, Fatma; Mihoğlugil, Feyyaz; Beutler, John A. A.; Eroğlu Özkan, Esra; Miski, Mahmut (MDPI, 2020)
Several simple and prenylated coumarin derivatives were isolated from the dichloromethane extract of the root of Neocryptodiscus papillaris based on moderate cytotoxic activity of the extract in COLO205, KM12 and MCF7 cancer cells. While the major prenylated furanocoumarin derivatives and osthol isolated from the dichloromethane extract were responsible for the activity in the colon and breast cancer cell lines, the 4'-acylated osthol derivatives including a novel coumarino-alkaloid; neopapillarine) demonstrated selective cytotoxic activity in A498 and UO31 renal cancer cell lines.
Keywords: Neocryptodiscus Papillaris; Apiaceae; Simple Coumarins; Furanocoumarins; Prenylated Coumarins; Coumarino-Alkaloid; Cytotoxic Activity